Numerical and Experimental Investigations of Laser Metal Deposition (LMD) Using STS 316L - Jaewoong Park; Jin-young Kim; Inseo Ji; Seung Hwan Lee (Applied Sciences, 2020)
This study aimed to understand the effect of heat accumulation on microstructure formation on STS 316L during multilayer deposition by a laser metal deposition (LMD) process and to predict the microstructure morphology. A comprehensive experimental and numerical study was conducted to quantify the solidification parameters (temperature gradient (G) and growth rate (R)) in the LMD multilayer deposition process. During deposition, the temperature profile at a fixed point in the deposit was measured to validate the numerical model, and then the solidification parameters were quantified using the model. Simultaneously, the microstructure of the deposit was investigated to confirm the microstructure morphology. Then, a relationship between the microstructure morphology and the G/R was proposed using a solidification map. The findings of this study can guide the design of scanning paths to produce deposits with a uniform structure.